A Shahname of 1612 C.E./1021 A.H. in the Persian Manuscript-Collection of the Library of the International Instittute of Islamic Thought and Civilization (ISTAC), Kuala Lumpur, Malaysia - Marcinkowski, Muhammad Ismail (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
A Shahname of 1612 C.E./1021 A.H. in the Persian Manuscript-Collection of the Library of the International Instittute of Islamic Thought and Civilization (ISTAC), Kuala Lumpur, Malaysia